2020
DOI: 10.1186/s12877-020-01922-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of falls among community-dwelling older people: results from three consecutive waves of the national health interview survey in Taiwan

Abstract: Background An aging society incurs great losses due to fall-related injuries and mortalities. The foreseeable increased burden of fall-related injury among older people requires a regular nationwide study on the fall epidemic and prevention strategies. Methods The fall epidemic was examined using data from three consecutive waves of the National Health Interview Survey (2005, 2009, and 2013). Common explanatory variables across these surveys includ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 37 publications
5
19
1
2
Order By: Relevance
“…This result is similar to that of Subramanian et al conducted in Indian outpatients aged >60 years [ 29 ]. However, the reported global fall rates in community-dwelling older people vary from 4% to 35% [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ], and the proportion of recurrent falls in our study is lower than those in the studies in developed countries [ 30 , 31 ]. These inconsistencies could be due to differences in culture, family structure and medical care conditions across countries.…”
Section: Discussioncontrasting
confidence: 85%
“…This result is similar to that of Subramanian et al conducted in Indian outpatients aged >60 years [ 29 ]. However, the reported global fall rates in community-dwelling older people vary from 4% to 35% [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ], and the proportion of recurrent falls in our study is lower than those in the studies in developed countries [ 30 , 31 ]. These inconsistencies could be due to differences in culture, family structure and medical care conditions across countries.…”
Section: Discussioncontrasting
confidence: 85%
“…Next, 1,177 studies were excluded during primary screening. After reviewing the texts of 107 articles, we excluded 73 studies, resulting in the inclusion of 34 articles [ 2 , 7 11 , 14 40 ]. In addition, we found four eligible studies from a previous review [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics of the studies are summarized in Table 1 [ 2 , 7 11 , 14 40 , 42 46 ]. The meta-analysis revealed that, overall, 27.6% of participants (n = 63,618) experienced falls.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations